THEORY OF PLANNED BEHAVIOR SEBAGAI PREDIKTOR INTENSI BERWIRAUSAHA - Yustina Chrismardani (Kompetensi (Competence : Journal of Management Studies), 2016)
Theory of Planned Behavior can not be separated from the entrepreneurial intention, because in this theory suggested that the formation of the behavior of entrepreneurs based on the conviction and evaluation to foster an attitude (attitude towards), subjective norms, and perceived behavioral control. This study examine the effect of the Theory of Planned Behavior to the entrepreneurial intention and also uses demographic factors to see whether there is any differences in the entrepreneurial intention based on gender, work experience, entrepreneurship  training experience and occupations of parents. Research conducted on students who are taking courses of Entrepreneurship, with a total sample of 66 people. From the analysis and hypothesis testing obtained the following conclusions: (1) Subjective norms, and perceived behavioral control affect the entrepreneurial intention, while the attitude towards has no effect to the entrepreneurial intention (2) entrepreneurial intention do not differ by gender, work experience, entrepreneurship  training experience and occupations of parents.